2021
DOI: 10.9734/ejnfs/2021/v13i730435
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Food Security Status and Coping Strategies to Food Insecurity among Rural Crop Farming Households in Ondo State, Nigeria

Abstract: This study examined the food security status and coping strategies to food insecurity of rural arable crop farming households in Ondo State, Nigeria. Primary data were used and a multistage sampling procedure was used to select 150 respondents. Food Security Index (FSI), Probit regression model and Coping Strategy Use Index (CSUI) were employed to carry out the analysis. The empirical findings revealed that (54%) of rural arable crop farming households in the study area were food secure based on the recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
4
5
0
Order By: Relevance
“…Of the remaining respondents, approximately 13.86% were not married, 1.43% were divorced. The results are in line with the studies of Adegoroye et al (2021) [1] , Badamosi et al (2023) [5] and Oluwalade et al (2023a) [14] who reported that married households are the majority in the area. The household heads ' educational level in particular is an important quantity that can influence the household solid waste social control activity (Oladosu et al, 2024) [10] .…”
Section: Demographic Features Of the Sampled Respondentssupporting
confidence: 92%
“…Of the remaining respondents, approximately 13.86% were not married, 1.43% were divorced. The results are in line with the studies of Adegoroye et al (2021) [1] , Badamosi et al (2023) [5] and Oluwalade et al (2023a) [14] who reported that married households are the majority in the area. The household heads ' educational level in particular is an important quantity that can influence the household solid waste social control activity (Oladosu et al, 2024) [10] .…”
Section: Demographic Features Of the Sampled Respondentssupporting
confidence: 92%
“…This result connotes instability of access to food among the sampled respondents. The results are similar to the findings of [26,34].…”
Section: Respondents' Food Security Statussupporting
confidence: 89%
“…On the other hand, largesize respondent has the potential of exerting pressure on respondent available resources such that affected respondent experiences reduction in their per capita food consumption or entertain anxiety of food shortage. This result is in in line with [23,27,34], who reported that large-size households are more food insecure than smallsize households.…”
Section: Socioeconomic Attributes Of the Respondentssupporting
confidence: 89%
“…This is a desirable development as training on any interventions that can be made available to the actors by any stakeholder may be easier. The performance of the entire value chain is enhanced when actors can read and write and obtain information by themselves cannot be over-emphasized (Kolade et al, 2020;Adegoroye et al, 2021). The mean farming experience was 18, 11, and 10 years for the producers, marketers, and processors, respectively.…”
Section: Results and Discussion Socioeconomic Characteristics Of The ...mentioning
confidence: 99%